Identification and comparison of characteristics of inflation rate in cities in Indonesia in the period of 2009–2014 with the period of 2014–2019 - Adi Setiawan; Bayu Wijayanto; Henry Junus Wattimanela (Faculty of Science and Mathematics, Universitas Kristen Satya Wacana, 2021)
This study aims to identify the characteristics of the MoM inflation rate in cities in Indonesia. In addition, it also compares the distribution of the monthly inflation rate for the 2009–2014 period with the 2014-2019 period in cities in Indonesia. The method used to identify the characteristics of the MoM inflation rate is by using summary of statistics, while to compare the distribution of the monthly inflation rate for the 2009–2014 period and the 2014–2019 period, the two-sample Kolmogorov-Smirnov test is used. Characteristics of the month to month (MoM) inflation rate in cities in Indonesia for the period October 2009 to March 2019 was presented. Furthermore, the comparison of the characteristics of the MoM inflation rate from October 2009 to September 2014 (period 1) and the period from October 2014 to March 2019 (period 2) was also shown. The cities of Banda Aceh, Kendari, Yogyakarta, Jakarta and Sorong had an average characteristic of inflation each month which tended to be low in February, March, April and September.Six cities had significantly different characteristics during period 2 inflation rate compared to period 1.